Evaluating gastrointestinal side effects and discontinuation rates of semaglutide in routine clinical practice: A prospective observational study. - Kodela, Monika Patel; Sasi , Dr.N.O.A.; Rao , Rama (Student’s Journal of Health Research Africa, 2025)
Background: Semaglutide, a GLP-1 receptor agonist, has demonstrated significant efficacy in glycemic control and weight reduction in Type 2 Diabetes Mellitus (T2DM). However, gastrointestinal (GI) side effects remain a common barrier to long-term adherence in real-world clinical practice. This study aimed to evaluate the prevalence, severity, and impact of gastrointestinal (GI) adverse events on discontinuation rates among patients initiated on semaglutide therapy. Methods: A prospective observational study was conducted on 100 adult T2DM patients prescribed semaglutide in a routine outpatient setting. Data on demographics, GI side effects (nausea, vomiting, diarrhea, constipation), severity grading (mild, moderate, severe), dose adjustments, and discontinuation rates were collected over a 12-week follow-up period. Descriptive statistics were applied to analyze frequency distributions. Results: The mean age of participants was 54.6 ± 10.8 years, with 52% being male. GI side effects were reported in 43% of patients. Nausea (28%) was the most common symptom, followed by vomiting (12%), diarrhea (10%), and constipation (6%). Multiple GI symptoms occurred in 14% of patients. Among affected individuals, 58.1% experienced mild symptoms, 27.9% required dose reduction for moderate symptoms, while 14% discontinued due to severe intolerance. The overall discontinuation rate was 9%, with GI side effects accounting for 6% of treatment cessations. Dose reductions were performed in 18% of patients, with 66.7% of them successfully continuing therapy post-titration. Conclusion: Gastrointestinal side effects are common but generally mild to moderate with semaglutide therapy. Proactive management, including gradual dose escalation and patient education, can mitigate side effects and improve adherence. Despite initial intolerance, most patients can continue therapy with appropriate interventions. Recommendations: Routine counseling, slow titration schedules, and early side-effect management strategies are crucial to optimize semaglutide adherence in clinical practice.